Vaccarin alleviates endothelial inflammatory injury in diabetes by mediating miR-570-3p/HDAC1 pathway - Li, Taiyue; Yu, Xiaoyi; Zhu, Xuerui; Wen, Yuanyuan; Zhu, Meizhen; Cai, Weiwei; Hou, Bao; Xu, Fei; Qiu, Liying (Frontiers in Pharmacology, 2022)
Vaccarin is a flavonoid glycoside, which has a variety of pharmacological properties and plays a protective role in diabetes and its complications, but its mechanism is unclear. In this study, we aim to investigate whether histone deacetylase 1(HDAC1), a gene that plays a key role in the regulation of eukaryotic gene expression, is the target of miR-570-3p in diabetic vascular endothelium, and the potential molecular mechanism of vaccarin regulating endothelial inflammatory injury through miR-570-3p and HDAC1. The streptozotocin (STZ)-induced diabetes mice model, a classical type 2 diabetic model, was established. The aorta of STZ-diabetic mice showed a decrease of miR-570-3p, the elevation of HDAC1 and inflammatory injury, which were alleviated by vaccarin. Next, we employed the role of vaccarin in regulating endothelial cells miR-570-3p and HDAC1 under hyperglycemia conditions in vitro. We found that overexpression of HDAC1 counteracted the inhibitory effect of vaccarin on inflammatory injury in human umbilical vein endothelial cells (HUVECs). Manipulation of miRNA levels in HUVECs was achieved by transfecting cells with miR-570-3p mimic and inhibitor. Overexpression of miR-570-3p could decrease the expression of downstream components of HDAC1 including TNF-α, IL-1β and MDA, while increase GSH-Px activity in HUVECs under hyperglycemic conditions. Nevertheless, such phenomenon was completely reversed by miR-570-3p inhibitor, and administration of miR-570-3p inhibitor could block the inhibition of vaccarin on HDAC1 and inflammatory injury. Luciferase reporter assay confirmed the 3′- UTR of the HDAC1 gene was a direct target of miR-570-3p. In summary, our findings suggest that vaccarin may suppress inflammatory injury in endothelial cells treated with high glucose by modulating the expression of miR-570-3p and HDAC1. Our study provides a new pathogenic link between deregulation of miRNA expression in vascular endothelium of diabetes and inflammatory injury.